Atopic dermatitis: disease characteristics and comorbidities in smoking and non‐smoking patients from the TREATgermany registry. (30th November 2021) - Pilz, A.C.; Schielein, M.C.; Schuster, B.; Heinrich, L.; Haufe, E.; Abraham, S.; Heratizadeh, A.; Harder, I.; Kleinheinz, A.; Wollenberg, A.; Wiemers, F.; Weisshaar, E.; et al.
Abstract: Background: Atopic dermatitis (AD) is a chronic inflammatory skin disease with a multifactorial genesis including genetic predispositions and environmental risk and trigger factors. One of the latter possibly is smoking, indicated by an increased prevalence of AD in adults and children that are actively or passively exposed to cigarette smoke. Objectives: In this study, AD characteristics and its atopic comorbidities are compared in smoking and non‐smoking AD patients. Methods: TREATgermany is a non‐interventional clinical registry which includes patients with moderate to severe AD in Germany. Baseline data of patients included in TREATgermany from inception in June 2016 to April 2020 in 39 sites across Germany was analysed comparing AD disease characteristics and comorbidities in smokers vs. non‐smokers. Results: Of 921 patients, 908 (male: 58.7%) with a mean age of 41.9 ± 14.4 reported their smoking status. The objective Scoring of Atopic Dermatitis (oSCORAD) did not differ between smokers ( n  = 352; 38.8%) and non‐smokers, however, lesions' intensity of oozing/crusts and excoriations as well as patient global assessment scores (PGA) of AD severity were higher in smoking as opposed to non‐smoking patients. Smokers reported a lower number of weeks with well‐controlled AD and more severe pruritus than non‐smokers. Total IgE levels were more elevated in smokers and they displayed a younger age at the initial diagnosis of bronchial asthma. After adjustment for potential confounders, the increased intensity of oozing/crusts, the reduced number of weeks with well‐controlled AD and the greater pruritus remained different in smokers compared to non‐smokers. In addition, smoking patients with adult‐onset AD showed a 2.5 times higher chance of involvement of the feet. Conclusions: German registry data indicate that AD patients who smoke have a higher disease burden with a different distribution pattern of lesions in adult‐onset AD. Abstract : Linked Commentary Valeria Aoki and Raquel Leão Orfali J Eur Acad Dermatol Venereol 2022; 36 : 324–325. https://doi.org/10.1111/jdv.17901 .